Neuropeptide expression and action in the reproductive system of the starfish Asterias rubens - Piñon Gonzalez, Victor M.; Feng, Yuling; Egertová, Michaela; Elphick, Maurice R. (Journal of comparative neurology (1911), 2024)
Reproductive processes are regulated by a variety of neuropeptides in vertebrates and invertebrates. In starfish (phylum Echinodermata), relaxin‐like gonad‐stimulating peptide triggers oocyte maturation and spawning. However, little is known about other neuropeptides as potential regulators of reproduction in starfish. To address this issue, here, we used histology and immunohistochemistry to analyze the reproductive system of the starfish Asterias rubens at four stages of the seasonal reproductive cycle in male and female animals, investigating the expression of eight neuropeptides: the corticotropin‐releasing hormone‐type neuropeptide ArCRH, the calcitonin‐type neuropeptide ArCT, the pedal peptide‐type neuropeptides ArPPLN1b and ArPPLN2h, the vasopressin/ocytocin‐type neuropeptide asterotocin, the gonadotropin‐releasing hormone‐type neuropeptide ArGnRH, and the somatostatin/allatostatin‐C‐type neuropeptides ArSS1 and ArSS2. The expression of five neuropeptides, ArCRH, ArCT, ArPPLN1b, ArPPLN2h, and asterotocin, was detected in the gonoducts and/or gonads. For example, extensive ArPPLN2h expression was revealed in the coelomic epithelial layer of the gonads throughout the seasonal reproductive cycle in both males and females. However, seasonal and/or sexual differences in the patterns of neuropeptide expression were also observed. Informed by these findings, the in vitro pharmacological effects of neuropeptides on gonad preparations from male and female starfish were investigated. This revealed that ArSS1 causes gonadal contraction and that ArPPLN2h causes gonadal relaxation, with both neuropeptides being more effective on ovaries than testes. Collectively, these findings indicate that multiple neuropeptide signaling systems are involved in the regulation of reproductive function in starfish, with some neuropeptides exerting excitatory or inhibitory effects on gonad contractility that may be physiologically relevant when gametes are expelled during spawning. The expression and action of neuropeptides in the reproductive system of the starfish Asterias rubens were investigated, as illustrated here for ArPPLN2h. This neuropeptide is expressed in the coelomic epithelial layer of the gonads [CE(Gd); arrowheads] in both female (a) and male (b) animals, and it causes relaxation of ovary (c) and testis (d) preparations in vitro.